2020
DOI: 10.1111/pim.12783
|View full text |Cite
|
Sign up to set email alerts
|

Status of IL‐4 and IL‐10 driven markers in experimental models of Visceral Leishmaniasis

Abstract: Aim Leishmania donovani, the causative agent for visceral leishmaniasis (VL), modulates host monocytes/macrophages to ensure its survival. However, knowledge regarding the host‐parasite interactions underpinning the disease remains limited. As disease progression is associated with polarization of monocytes/macrophages towards M2, which is regulated by cytokines IL‐4/IL‐13 and IL‐10, this study evaluated the status of key IL‐4‐ and IL‐10 driven markers in experimental models of VL, as also evaluated their corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…In fact, we have elucidated a strong positive correlation between interleukin-10 production and parasitic load, that is, there was no control of tissue parasitism in those animals whose IL-10 levels were high. Similarly, studies elucidated that spleen from hamsters infected presented a gradual increase in interleukin-10 ( Melby et al, 1998 ; Moulik et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we have elucidated a strong positive correlation between interleukin-10 production and parasitic load, that is, there was no control of tissue parasitism in those animals whose IL-10 levels were high. Similarly, studies elucidated that spleen from hamsters infected presented a gradual increase in interleukin-10 ( Melby et al, 1998 ; Moulik et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data corroborate with these concepts, whereas we observed a high spleen parasitism accompanied by lower percentage of IFN- γ and increased levels of IL-10 in infected and untreated hamsters (IA group) (Figs 2, 4 and Table 1). Similarly, other studies also showed the growth of IL-10 expression in hamsters infected (Medina-Colorado et al ., 2017; Moulik et al ., 2021). Beyond that, a strong positive correlation was found between the reduction of the splenic parasite burden and T-CD4 + IL-10 + lymphocytes levels reduced in LBSapMPL and Milt-LBSapMPL groups (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Another cytokine that plays an important suppressive role in VL is IL-10, and its role in the progression of visceral disease is already well established in both murine and human models. High levels of IL-10 are associated with a higher parasite load and are related to the development of the most severe form of disease ( 61 , 133 , 134 ). Both BALB/c and C57BL/6 mice lacking IL-10 due to either gene deletion or blockade using specific antibodies are resistant to Leishmania and do not develop the clinical manifestations of the disease ( 135 – 137 ).…”
Section: Cytokinesmentioning
confidence: 99%